Media, religion and culture : an introduction - Mahan, Jeffrey H.; Thrall, James Homer, 1956- (Routledge, 2026)
"Religion has always been shaped by the media of its time. Religious individuals, communities and institutions use media as tools to communicate, but also as locations where they construct and express identity, practice religion, and build community. This lively book offers a comprehensive introduction to the contemporary field of religion, media, and culture. It explores the religious content of media texts and the reception of those texts by religious consumers who appropriate and reuse them in their own religious work, and considers how new forms of media provide fresh locations for new religious voices and identities to emerge. Thoroughly updated throughout, the book features case study examples from both established and new religions, and each chapter is followed by insightful reflections from leading scholars in the field. Illustrated throughout, the book also contains discussion questions and a glossary of key terms"--